O Uso de simulações virtuais como potencial pedagógico no ensino de Ciências - LUZ, Lays Maria Nunes da (2023)
This extensionist work aims to stimulate, through scientific dissemination, the use of virtual simulators, through interactive actions using virtual (computer) simulation environments, such as: PhET, Physics at School and among others. This work is characterized as a case study, whose research was carried out with teachers in training linked to the following courses: degree in Natural Sciences, from the Institute of Coastal Studies, from the Federal University of Pará (UFPA) - Campus of Bragança (IECOS / UFPA - Campus of Bragança); degree in Physics, from UFPA - Campus of Ananindeua; and degree in Natural Sciences, from IECOS/ UFPA - Campus de Bragança - Polo Santa Luzia do Pará, through presentations made via Google Meet. In addition, online questionnaires were carried out via the Google Forms platform with the participation of 43 students in total, as an attempt was made to understand the particularities and complexities involved in the studied situation. The research results led to a better understanding of the use of Digital Information and Communication Technologies (DICT) in science teaching, especially regarding the importance of these tools in enabling educational practices.